Electromagnetic scattering of a plane wave by a perfectly conducting elliptic cylinder near a plane surface. (July 2023) - Santini, Carlo; Mangini, Fabio; Frezza, Fabrizio
Highlights: We present a rigorous method to evaluate the scattering of a plane electromagnetic wave by a perfectly conducting elliptic cylinder parallel to a generally reflecting plane surface. The solution is based on the Spectral Domain method and the plane-wave expansion of the elliptical cylindrical waves. The surface is characterized by means of a reflection coefficient. The analytical method is implemented in specific computational code to achieve a numerical solution. Results are validated by means of a finite element method commercial software. Validation trials, show good agreement between the two independent computational methodologies. Abstract: In this paper, we present a rigorous analytical and numerical method to evaluate the scattering of a plane electromagnetic wave by an infinite, perfectly conducting elliptic cylinder parallel to a non-perfectly reflecting plane surface. The analytical solution is based on the spectral domain method and the plane-wave expansion of the elliptic cylindrical waves and is applicable in a broad variety of cases in which the properties of the plane surface may be expressed by means of a reflection coefficient. The proposed approach is suitably implemented in a specific computational code to achieve a numerical solution. Results of validation trials, performed by using finite element method commercial software, are provided.